The Role of the Micro, Small and Medium Enterprises Office in the Development of Small and Medium Enterprises After the Covid-19 Pandemic in Pontianak City - Awaluddin, M.; Qadri, Ul; Zulianto, Didi (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2022)
The COVID-19 pandemic has had a profound impact on people in all walks of life and sectors of life. The impact felt by the community is not only limited to the public health sector, but also includes other sectors such as the economy and education. The economic sector is marked by a decrease in MSME income due to the policy of limiting social interaction. The existence of the COVID-19 pandemic that entered Indonesia caused various sectors to be affected by the large-scale social restrictions (PSBB) regulations, one of which was the decline in the income of MSME business actors. nationally around 2.97%. The purpose of this study was to determine the role of the Office of Cooperatives for Micro, Small and Medium Enterprises in Pontianak City in the development of MSME business actors. The research method used is descriptive qualitative research with a study study approach, data sources come from interviews with informants, observation and documentation. The data analysis technique used is interactive model analysis (Miles and Huberman). The results of the study found that during the COVID-19 pandemic, MSME actors used social media for promotion so that they persisted, while after the pandemic the MSME Service provided socialization to provide information on where to market MSME products. In addition, the MSME Service held an exhibition of MSME products to increase sales after the COVID-19 pandemic. As a result, MSMEs in Pontianak City are better and running normally as usual after the COVID-19 pandemic.